2015
DOI: 10.1002/celc.201402454
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Conversion of Dichloroacetic Acid to Chloroacetic Acid in a Microfluidic Stack and in a Series of Microfluidic Reactors

Abstract: In the black: a chromic change of Pd‐doped V2O5 nanowires from orange to black occurred after exposure to molecular hydrogen at room temperature. The change in color is irreversible and attributed to a hydrogen spillover effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Owing to the development of diamond-based anode, higher degree of electrochemical oxidation of organic contaminants has been reached [8,9]. Furthermore, the application of microfluidic reactor within the framework of EAOPs has spurred the capability of wastewater treatment [10][11][12][13][14]. It allows mineralization of organic pollutants without the addition of supporting electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the development of diamond-based anode, higher degree of electrochemical oxidation of organic contaminants has been reached [8,9]. Furthermore, the application of microfluidic reactor within the framework of EAOPs has spurred the capability of wastewater treatment [10][11][12][13][14]. It allows mineralization of organic pollutants without the addition of supporting electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the main charge carriers will also be a generated halide anion and a ferrrocenium cation. Although many investigations of small-scale PPERs focus on the synthetic possibilities [11][12][13][14][15] or on cell-design and scale-up [16][17][18][19][20][21], few modeling studies have been reported which are applicable to self-supported paired synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that microfluidic reactors can improve the electrochemical processes for the treatment of wastewaters contaminated by recalcitrant pollutants and the synthesis of chemicals . Thus, microfluidic electrochemical devices, presenting very small distances between electrodes, can offer several important advantages such as:…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the possibility given by micro‐cells, of operating in a continuous mode, enables the use of more electrochemical microfluidic reactors in series, making it also possible to have an independent choice of the electrodic processes confined within each of them. This possibility was recently investigated in the frame of the synthesis of chemicals . It was shown that the adoption of microreactors in series can allow, on the one hand, an increase in the productivity of the process (as a result of higher electrode surfaces) and, on the other hand, different operating conditions to be used in the reactors, thus allowing us to improve the figures of merit of the process in terms of conversion and selectivity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation